NON-CRYOGENIC PRESERVATION ON GROUPER MUSCLE TISSUE FOR DNA ANALYSIS - Andi Parenrengi (Research Center for Fisheries, 2002)
Sample preservation is one of the problems frequently faced in collecting materials such as muscle tissue and blood samples in the field and during transportation to the laboratory prior to DNA extraction.